Assessment of a Multiagency Approach to Drug-Involved Gang Members in San Diego County, California, 1988-1992 - Pennell, Susan ([Verlag nicht ermittelbar], 2000)
In 1988, with funds from the Bureau of Justice Assistance (BJA) via the Anti-Drug Abuse Act of 1987, a multiagency task force, Jurisdictions Unified for Drug Gang Enforcement (JUDGE), was created. Spearheaded by the San Diego County District Attorney's Office and representing a unique blend of police officers, probation officers, and deputy district attorneys working together, the JUDGE program targeted documented gang members also involved in drug use and sales. The task force incorporated an intensive supervision approach that enforced conditions of probation and drug laws and provided vertical prosecution for probation violations and new offenses involving targeted offenders. This research project sought to address the following research objectives: (1) to determine if the JUDGE program objectives were met during the grant period, (2) to assess the results of program activities, such as surveillance, special enforcement, and vertical prosecution, in terms of probation violations, arrests, pretrial custody, probation revocations, convictions, and sentences, (3) to evaluate the impact of the program on offenders as measured by recidivism and the need for probation intervention, (4) to assess the cost of JUDGE probation compared to regular probation caseloads, and (5) to provide recommendations regarding the implementation of similar programs in other jurisdictions. This research project consisted of a process evaluation and an impact assessment that focused on the first two years of the JUDGE program, when youthful offenders were the targets (1988 and 1989). The research effort focused only on new targets for whom adequate records were maintained, yielding a study size of 279. The tracking period for targets ended in 1992. For the impact assessment, the research was structured as a within-subjects design, with the comparison focusing on target youths two years before the implementation of JUDGE and the same group two years after being targeted by JUDGE. Data were compiled on the juveniles' age at target, race, sex, gang affiliation, type of target (gang member, drug history, and/or ward), status when targeted, and referrals to other agencies. Variables providing data on criminal histories include age at first contact/arrest, instant offense and disposition, highest charges for each subsequent arrest that resulted in probation supervision, drug charges, highest conviction charges, probation conditions before selection date and after JUDGE target, number of contacts by probation and JUDGE staff, number of violations for each probation condition and action taken, and new offenses during probation. For the process evaluation, case outcome data were compared to project objectives to measure compliance in terms of program implementation and results. Variables include number of violations for each probation condition and action taken, and number of failed drug tests. The consequences of increased probation supervision, including revocation, sentences, custody time, and use of vertical prosecution, were addressed by comparing the processing of cases prior to the implementation of JUDGE to case processing after JUDGE targeting.